RANCANG BANGUN APLIKASI MANAJEMEN ASET BERBASIS WEBSITE PADA SMA HANG TUAH 4 SURABAYA - Rahmat Julianto Putra; Endra Rahmawati; Nunuk Wahyuningtyas (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
The fixed assets at SMA Hang Tuah 4 Surabaya are managed by the Wakasapras (Facilities and Infrastructure) Section. Asset data collection carried out is recording asset codes, recording origin codes, asset management, asset repair, asset maintenance, asset deletion, asset management is currently still manual or written in books and some asset data is also recorded in Microsoft Excel and stored on the flash if there are new assets that come then the wakasapras section will collect data on asset management. However, if it is still written in a book or typed in Microsoft Excel, it causes errors when recording asset management, sometimes there are two data that are the same when collecting data or sometimes they do not match the original, so there is the same data with different asset descriptions. . For the asset repair process, school officials will collect asset data to be repaired in paper form which will then be given to the wakasapras section as evidence that there are damaged assets and must be repaired immediately.Then for the asset maintenance process, the current process is that there is no asset maintenance, for asset maintenance it is only done when an asset is damaged. The absence of asset maintenance causes the assets in Hang Tuah 4 Surabaya High School to be damaged quickly and incur ongoing costs. Even this asset maintenance that has been carried out is still not recorded, so the wakasapras section and officers do not know which assets are often damaged and what costs are incurred, while for the asset removal process carried out by the wakasapras section and this officer destroys assets that have been damaged. no longer suitable for use or no longer functioning for the needs of Hang Tuah 4 High School Surabaya. However, there are problems that occur when the assets are written off by the wakasapras and officers. There are also assets that have been deleted that are not recorded, so the wakasapras and officers do not know how many assets have been deleted and what assets have been deleted.Based on the problems above, a website-based asset management application was made at SMA Hang Tuah 4 Surabaya to help and facilitate the wakasapras and school officers in carrying out asset data collection which consists of recording asset codes, asset receipts, asset repair, asset maintenance, asset deletion.Keywords: Asset management, Asset repair, Asset maintenance, Asset deletion.